Effect of magnetic field on peroxidase activities of soybean tissue culture - Olgun, Atok; Alikamanoğlu, Sema; Rzakoulieva, A.; ATAK, ÇİMEN; ÇELİK, ÖZGE (DIAGNOSIS PRESS LTD, 67 DONDUKOV BLVD, 1504 SOFIA, BULGARIA, 2007)
In this study, the aim was to determine the effect of magnetic field on peroxidase activities of soybean tissue culture. Shoot tips were put into petri dishes and exposed to a magnetic field for a period of 2.2 and 19.8 s at a magnetic flux of 2.9-4.6 mT. The shoot and root formation rate, fresh weights, chlorophyll quantities, total RNA concentrations and peroxidase activities of regenerated shoots from control and treated shoot tips were determined. While the rate of shoot formation was 28.57% in the control group, this rate was increased to 94.33% and 78.18%, respectively, in the explants that were exposed to a magnetic field for a period of 2.2 and 19.8 s. While the percentage of root formation in controls was 4.76%, this rate increased to 47.17% and 54.54%, respectively, in those that were exposed to a magnetic field at the same periods. When the fresh weights were determined, we found that the fresh weights of plantlets regenerated from treated explants were increased relative to controls. Chlorophyll a, chlorophyll b and total chlorophyll contents increased 21%, 13% and 18%, respectively, relative to control groups at 2.2 s. Peroxidase activity significantly increased in all magnetic field treatments (p<0.05). The total RNA concentration of seedlings regenerated from treatment explants significantly increased relative to controls (p<0.05). The regeneration and plant growth of shoot tips exposed to a magnetic field with a 2.2 s period were positively affected by the MF and increased with respect to controls and the length of time exposed.
Keywords: soybean; magnetic field; in vitro regeneration; peroxidase activity; acid; transcription; oxidase; growth; plants; roots; cells; auxin; soya fasulyesi; manyetik alan; in vitro rejenerasyon; peroksidaz aktivitesi; asit; transkripsiyon; oksidaz; büyüme; bitkiler; kökleri; hücreler; oksin